(untitled) (Global Journal of Human-Social Science, 2016)
The aims of this study are to measure the technical efficiency (TE) of Cambodian household’s rice production and its main influencing factors using SFA model. Primary data was collected from 301 rice farmers in three selected districts of Battambang by structured questionnaires. The empirical results indicated the mean TE is 0.34 which means famers produce 34% of rice at best practice at the current level of production inputs and technology, reveling that rice output has the potential of being increased further by 66% at the same level of inputs if farmers had been technically efficient. Evidence also reveals that land, fertilizer, and pesticide are the major influencing input factors of household’s rice production. However, between 2013 and 2015 TE recorded -14.3% decline rate due to highly affected of drought during dry season of 2015.